Application of poroelastic layers in a semi-submersible platform: Devising an efficient heave motion response reduction method. (1st April 2020) - Emami, Arefeh; Mostafa Gharabaghi, Ahmad Reza
Abstract: This paper describes an efficient and applicable approach to decrease the heave motion response of a semi-submersible platform by introducing poroelastic layers (PELs) at the bottom of its pontoons. This study was carried out utilizing a semi-analytical method based on eigenfunction expansion, which involves determining the added mass, damping, related hydrodynamic force and heave motion response. The adequacy of the semi-analytical method was verified by applying it to a typical GVA4000 drilling semi-submersible platform, whose heave response amplitude operator was extracted and compared with available experimental data. The extracted value and available data showed close agreement. Furthermore, the effectiveness of the PELs attached at the bottom of the GVA4000 drilling semi-submersible platform and the effect of PEL characteristics such as the thickness, intrinsic permeability, and elasticity on reducing heave motion response were evaluated. Comparing the results with the studied GVA4000 drilling semi-submersible platform without PELs indicated that the application of PELs could considerably reduce the heave motion response and nearly eliminate the risk of creating a resonance phenomenon in the semi-submersible platforms in different sea wave conditions. The approach introduced in this study could be a suitable pathway to improve the performance of semi-submersible platforms, particularly their heave motion responses. Highlights: Concept of poroelastic layers (PELs) is proposed. Eigenfunction expansion method is applied to obtain the solutions. Effect of PELs on heave motion response of a semi-submersible platform is studied. Effect of thickness, intrinsic permeability, and elasticity of PELs is evaluated. Results are compared with those of a platform without attached PELs.